Eimeria Species (Apicomplexa: Eimeriidae) from Anatolian Ground Squirrels (Spermophilus xanthoprymnus) in Turkey - Utuk, Armagan Erdem; Simsek, Sami; Koroglu, Ergun; Dumanli, Nazir (Kafkas Univ, Veteriner Fakultesi Dergisi, 2010)
This study was conducted to determine the Eimeria species of Anatolian ground squirrels (Spermophilus xanthoprymnus). Eimeria spp. oocysts were found in all (100%) of seven fecal samples examined by zinc sulphate flotation method. Eimeria morainensis, E. callospermophili, and E. lateralis were detected in Anatolian ground squirrels in Turkey for the first time.
Türkiye'de Anadolu Yer Sincaplarinda (Spermophilus Xanthoprymnus) Bulunan Eimeria (Apicomplexa: Eimeriidae) Türleri
Keywords: Anatolian ground squirrel; Eimeria; Spermophilus xanthoprymnus; Turkey